Comparative Effects of Three Seventh-Grade Science Programs with Different Laboratory Materials. - Stronck, David R. (Science Education)
The article discusses a study of a science in-service program conducted in the parochial schools of the Archdiocese of San Francisco in California. In the academic year of 1966 to 1967, most of the seventh-grade students were receiving little or no instruction in science. Students of seven schools were selected as the representative sample of the entire population of students receiving benefits from the science in-service program. Results of the study led to the conclusions that a quantitative general science course provides less scientific facts and processes than a descriptive general science course and an in-service program can suddenly introduce a new laboratory-centered program into all the schools of a large district.